From the shallow to the mesophotic: a characterization of Symbiodiniaceae diversity in the Red Sea NEOM region - Terraneo, Tullia I.; Ouhssain, Mustapha; Castano, Carolina Bocanegra; Aranda, Manuel; Hume, Benjamin C. C.; Marchese, Fabio; Vimercati, Silvia; Chimienti, Giovanni; Eweida, Ameer A.; Voolstra, Christian R.; Jones, Burton H.; Purkis, Sam J.; et al. (Frontiers in Marine Science, 2023)
Introduction The northern Red Sea has been coined a refuge for reef corals due to the exceptional thermal tolerance of these organisms. With ocean warming threatening coral reefs worldwide, a panoptic characterization of corals living in extreme conditions may provide insights into future responses of corals to environmental change. Among other factors, the genotype of the endosymbiotic algae in the family Symbiodiniaceae has been shown to have major implications on the distribution and resilience of their coral hosts. In this study, we aim at genotyping the Symbiodiniaceae communities associated with three depth generalist and one depth specialist coral species, characterized by the ability to withstand environmental conditions that are apparently limiting for other corals and occurring in a unique geographical region. Methods We sampled 50 corals from the northern Saudi Arabian Red Sea and the Gulf of Aqaba, covering a 97 m bathymetric gradient. We used high-throughput ITS2 gene sequencing and recovered different patterns of host–algal associations. Results and discussion The majority of the recovered algal genotypes appeared host- and environment-specific, while others were more widely distributed. At large, coral specimens were overwhelmingly associated with symbionts from the genus Cladocopium and specifically with many previously undescribed genotypes. This suggests the selection of specific genotypes, which might confer resistance and/or resilience to their host counterparts. Interestingly, we found a limited association with Durusdinium spp. and other known tolerant taxa in mesophotic corals in the northern Red Sea, but not in the Gulf of Aqaba. The broad absence of Durusdinium spp., typically ascribed to be stress tolerant, warrants further investigation into Symbiodiniaceae species that convey environmental resilience. Our data will serve as a baseline to explore the occurrence of specific symbionts that might be contributing to coral acclimation and adaptation and to assay how biodiversity might be impacted if subjected to increasing stressors.